INNOVATIVE METHODS IN ORGANIZING EDUCATIONAL ACTIVITIES AND PROBLEMS IN THEIR IMPLEMENTATION - Niyozhon Ilyozhonugli Ergashov (Web of Journals Publishing, 2023)
The article describes innovative methods and problems in their implementation in the organization of modern educational activities. There is also a focus on the importance of independent educational activities in education.
Keywords: pedagogical activity, technology, innovative technology, independent education, educational process, intellectual potential, practical activity.